Smart discipline for the classroom : respect and cooperation restored - Koenig, Larry (Thousand Oaks, Calif. Corwin Press, 2000)
No matter what the need or situation, Koenig provides methods that are varied, adaptable, and easily tailored to fit any instructor's teaching style and any student's personality.
Includes bibliographical references and index.
Keywords: School discipline -- United States; Classroom management -- United States